Fibrin-Associated Diffuse Large B Cell Lymphoma Found on Revision Arthroplasty of the Knee. Issue 11 (November 2021) - Hall, Jordan; Kampfer, Craig; Williams, Ned; Osswald, Michael; Bishop, Bradie; Hall, Misty; Alderete, Joseph
Abstract : Abstract: Fibrin-associated diffuse large B cell lymphoma (FA-DLBCL) is a rare Epstein-Barr viruspositive B cell lymphoma that is nonmass-forming, does not directly produce symptoms, and is incidentally discovered on histological examination of tissues excised for other reasons. Despite overlap in morphologic and immunophenotypic features with aggressive B cell neoplasms, FA-DLBCL shows an excellent clinical outcome, even with surgical excision alone. We report an extremely rare occurrence of FA-DLBCL found in association with a metallic implant on revision arthroplasty of the knee. This report also illustrates the need for an integrated multidisciplinary approach for accurate diagnosis and avoidance of overtreatment. Abstract : Fibrin-associated diffuse large B cell lymphoma is a rare non-Hodgkin lymphoma that is nonmass forming, does not directly produce symptoms, and is discovered incidentally on histological examination of tissues excised for other reasons. This article illustrates the need for a multidisciplinary approach to a patient with fibrin-associated diffuse large B cell lymphoma incidentally identified on revision arthroplasty of the knee.